The relationship between health literacy and perceived shared decision making in patients with breast cancer. Issue 2 (February 2019) - Shen, Hsiu-Nien; Lin, Chia-Chen; Hoffmann, Tammy; Tsai, Chia-Yin; Hou, Wen-Hsuan; Kuo, Ken N.
Highlights: Health literacy include healthcare, disease prevention, and health promotion domains. 3-domain Health literacy more important than other factors on shared decision making. Age and education modify relationship of health literacy and shared decision making. Abstract: Objectives: We explored the relationship between patient-perceived shared decision making (SDM) and three domains of health literacy (HL) in patients with breast cancer. Methods: In this cross-sectional study, we prospectively recruited a convenience sample of 511 breast cancer patients from 3 hospitals in Taiwan. Patients completed questionnaires about HL and perceived SDM in a recent consultation. Sequential regressions, controlling for International Classification of Functioning, Disability and Health (ICF)-related factors) were conducted. Interactions of each HL domain with age or education were also assessed for the relationship with perceived SDM. Results: Higher scores in the HL domains of healthcare and disease prevention, but lower scores in the health promotion domain, were significantly associated with a higher perceived level of SDM after controlling for ICF-related factors (R 2 = 33.44%). The association of SDM with two domains of HL varied with age, while the relationship between the 3 HL domains and SDM differed across education levels. Conclusion: Each HL domain was significantly associated with perceived SDM after controlling for the ICF-related factors and across different age- and education-stratifications. Practice implications: Clinicians should be cognizant of patients' HL levels and incorporate HL best practices into consultations and interactions with patients with breast cancer to facilitate SDM.